Network-on-Chip Irregular Topology Optimization for Real-Time and Non-Real-Time Applications - Samuel da Silva Oliveira; Bruno Motta de Carvalho; Márcio Eduardo Kreutz (Micromachines, 2021)
Network-on-Chip is a good approach to working on intra-chip communication. Networks with irregular topologies may be better suited for specific applications because of their architectural nature. A good design space exploration can help the design of the network to obtain more optimized topologies. This paper proposes a way of optimizing networks with irregular topologies through the use of a genetic algorithm. The network proposed here has heterogeneous routers that aim to optimize the network and support applications with real-time tasks. The goal is to find networks that are optimized for average latency and percentage of real-time packets delivered within the deadline. The results show that we have been able to find networks that can deliver all the real-time packets, obtain acceptable latency values, and shrink the chip area.